2021
DOI: 10.1016/j.ajhg.2021.04.009
|View full text |Cite|
|
Sign up to set email alerts
|

Sub-genic intolerance, ClinVar, and the epilepsies: A whole-exome sequencing study of 29,165 individuals

Abstract: Both mild and severe epilepsies are influenced by variants in the same genes, yet an explanation for the resulting phenotypic variation is unknown. As part of the ongoing Epi25 Collaboration, we performed a whole-exome sequencing analysis of 13,487 epilepsy-affected individuals and 15,678 control individuals. While prior Epi25 studies focused on gene-based collapsing analyses, we asked how the pattern of variation within genes differs by epilepsy type. Specifically, we compared the genetic architectures of sev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 127 publications
3
29
0
Order By: Relevance
“…S11). A previous similar analysis of this [10] and related [11] datasets examined loss-of-function intolerant genes and demonstrated an increased burden in ultra-rare constrained as well as protein truncating variants (PTVs). Here, the examination of brain-expressed intolerant genes showed, similarly, a marked enrichment in PTVs in addition to a burden in highly constrained missense variants that is comparable to what is seen exome-wide ( Figs.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…S11). A previous similar analysis of this [10] and related [11] datasets examined loss-of-function intolerant genes and demonstrated an increased burden in ultra-rare constrained as well as protein truncating variants (PTVs). Here, the examination of brain-expressed intolerant genes showed, similarly, a marked enrichment in PTVs in addition to a burden in highly constrained missense variants that is comparable to what is seen exome-wide ( Figs.…”
Section: Resultsmentioning
confidence: 85%
“…We analyzed subjects from recruitment years 1 and 2 ( n = 13,197 before filtering) targeting individuals diagnosed with DEE ( n = 1,474), GGE ( n = 4,510), NAFE ( n = 5,321). The epilepsy classification, phenotyping and consent procedures have been previously described [ 10 , 11 ]. Five control cohorts [ 10 , 12 ] were available for this analysis ( n = 13,299), including Italian controls from the Epi25 Collaborative ( n = 300), the Swedish Schizophrenia Study controls ( n = 6,242), and three Myocardial Infarction Genetics (MIGen) Consortium cohorts: Leicester UK Heart Study ( n = 1,165), Ottawa Heart Study ( n = 1,915) and the Italian Atherosclerosis, Thrombosis, and Vascular Biology (ATVB) Study ( n = 3,677).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, thousands of genes have been reported as associated with epileptic conditions(Epi25 Collaborative. Electronic address & Epi, 2021;Fatima et al, 2021;Fry et al, 2021;Li et al, 2021;Lindy et al, 2018;Liu et al, 2018;Parrini et al, 2017;Tidball et al, 2020;Usmani et al, 2021), but most of them are not experimentally confirmed (Ran et al, 2015;Stenson et al, 2017;Takata et al, 2019;. Considering that comprehensive epilepsy panels including hundreds of genes are offered by companies for genetic counseling (Poduri, 2017;, it is imperative to perform mechanistic studies and confirm genotype-phenotype associations to assist clinicians in proper diagnosis and therapeutic decisionmaking (Ellis et al, 2020).…”
Section: Introductionmentioning
confidence: 99%